Dry Thermal Insulation of Thick Clothing - Fourt, Lyman; Lyerly, George A; Edwards, Grant C; Poland, Eleanor D (1960)
This report presents a physical analysis of an insulated cylinder system in use in this laboratory and insulating values or thermal resistances per unit thickness obtained on certain types of clothing materials under dry conditions. The over-all heat flow rates, or over-all thermal resistance of clothing assemblies, which have been used for greater-than-or-less-than comparisons in previous reports, have been refined to come closer to being measurements of the thermal resistance of particular layers, by making more accurate corrections for heat losses through the insulated ends of the test equipment, and by measuring temperature gradients through the clothing itself. As a system for measuring thermal resistance, the cylinder used in this laboratory is best suited to layers ranging in thickness from 0.2 to 2.0 or 2.5 cm. This extends to heavy arctic or flying clothing. The intrinsic thermal resistance of a polyurethane foam was found to be 0.30 degree C sq.m/watt cm or 4.9 Clo per inch. This appears to be more insulation per unit thickness than for woven fabrics. White the usual 'practical' value for clothing plus air layers is 4 Clo/inch, the thermal conductivity for still air is close to 7 Clo per inch, so these thick, low density layers of foams or batts may offer a real increase in insulation over woven or knitted textile structures.